Raising Student Enrolment in Government Schools: The Way Forward - Srinivas , Kadem (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The enrolment in government schools is sharply dropping due to various reasons such as accountability of teachers, small schools which have fewer teachers and not providing quality education, etc. Many of the elementary schools in India are started and operating in remote, tribal, rural and hilly areas to provide easy accessibility of education to every child and majority of these schools are running with low enrolment. The idea of merging (clubbing) and consolidation of small schools transforms in to one common school and establish at nearby common locality (habitation) may lead to tremendous changes in Indian School Education System. This idea has several benefits such as one class one teacher, less financial burden to government, etc. Fulfilling parental aspirations and expectations is also one of the key elements to improve the enrolment in government schools. This paper explores the way of possibilities to improve the enrolment in government schools.